2006
DOI: 10.1029/2005jd006047
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of spectroradiometers and Sun photometers for the determination of the aerosol optical depth during the VELETA‐2002 field campaign

Abstract: [1] In July 2002 the VELETA-2002 field campaign was held in Sierra Nevada (Granada) in the south of Spain. The main objectives of this field campaign were the study of the influence of elevation and atmospheric aerosols on measured UV radiation. In the first stage of the field campaign, a common calibration and intercomparison between Licor-1800 spectroradiometers and Cimel-318 Sun photometers was performed in order to assess the quality of the measurements from the whole campaign. The intercomparison of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 32 publications
4
55
0
Order By: Relevance
“…6) between the two instrument datasets results in a high R 2 (ranging between 0.768 at 870 nm and 0.940 at 500 nm) and an RMSE of between 0.040 (675 nm) and 0.075 (400 nm). This is similar to differences found between LICOR LI1800 spectrometers (Estellés et al, 2006). The 400 nm channel performance was somewhat worse than the other wavelengths using the RMSE Figure 6.…”
Section: Correcting Data For Different Field-of-view Anglessupporting
confidence: 72%
See 1 more Smart Citation
“…6) between the two instrument datasets results in a high R 2 (ranging between 0.768 at 870 nm and 0.940 at 500 nm) and an RMSE of between 0.040 (675 nm) and 0.075 (400 nm). This is similar to differences found between LICOR LI1800 spectrometers (Estellés et al, 2006). The 400 nm channel performance was somewhat worse than the other wavelengths using the RMSE Figure 6.…”
Section: Correcting Data For Different Field-of-view Anglessupporting
confidence: 72%
“…9). While not perfect, this is approaching the uncertainty of AERONET fielddeployed CIMEL instruments (0.01-0.02) and the level of agreement between different sun photometers when they are compared together in the field (0.01-0.02) using different AOD methodologies (Estellés et al, 2006). LICOR 1800 spectroradiometers calibrated by lamps also have a nominal AOD uncertainty of about 0.02-0.05 (Estellés et al, 2006).…”
Section: Correcting Data For Different Field-of-view Anglesmentioning
confidence: 99%
“…In our case the error in the AOD is mainly conditioned by the error in the measurement of the direct spectral irradiance and the value of the optical air mass in the instant of the measurement. The authors have previously used this method with experimental measurements made at other sites [42] and the values that were obtained were similar to those presented by Kaufman et al [43].…”
Section: Aerosol Optical Depthsupporting
confidence: 72%
“…Nevertheless Estelle´s et al [42] compared the Licor 1800 and Cimel 318 (instrument used in AERONET) results obtained in Veleta 2002 campaign. They concluded that the deviation in the retrieved AOD between both instruments in the visible range is 0.01-0.03, depending on the channel.…”
Section: Aerosol Optical Depthmentioning
confidence: 99%
“…The calibration measurements were carried out on completely cloud free days, with low and stable aerosol concentration. The total uncertainty in aerosol optical depth is <±0.02 (Estellés et al, 2006).…”
Section: Instruments and Measurementsmentioning
confidence: 88%